2012
DOI: 10.1007/s10499-012-9499-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative histopathological, immunohistochemical and nested-PCR study for diagnosis of infectious pancreatic necrosis in the naturally infected cultured rainbow trout (Oncorhynchus mykiss)

Abstract: To confirm the diagnosis of the infectious pancreatic necrosis, the pancreas, liver, kidney and spleen specimens from 140 rainbow trout (Oncorhynchus mykiss) of weight ranges from 15 to 250 g were processed for routine histopathological and immunohistochemical (IHC) studies together with a nested-PCR using primers that amplify a 164-bp product. Of the 140 fish samples, 37 (26.4%) had a final diagnosis of IPN on the basis of hematoxylin and eosin staining (H&E), while 39/45 (86.6%) were positive by IHC method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Based on these studies, the IPNV isolates included in this study should be nearly avirulent, with Ala, Thr, and Glu amino acid residues at positions 217, 221, and 247, respectively. However, despite the presence of Thr at position 221 in Iranian isolates of IPNV (Dadar et al 2013), the observed mortality among naturally infected Rainbow Trout fry corresponds to that caused by moderately virulent isolates (Raissy et al 2010;Oryan et al 2012;Ahmadi et al 2013). Similarly, Rainbow Trout naturally infected with MEX2-CSM-05 showed signs of infectious pancreatic necrosis, including mortality (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these studies, the IPNV isolates included in this study should be nearly avirulent, with Ala, Thr, and Glu amino acid residues at positions 217, 221, and 247, respectively. However, despite the presence of Thr at position 221 in Iranian isolates of IPNV (Dadar et al 2013), the observed mortality among naturally infected Rainbow Trout fry corresponds to that caused by moderately virulent isolates (Raissy et al 2010;Oryan et al 2012;Ahmadi et al 2013). Similarly, Rainbow Trout naturally infected with MEX2-CSM-05 showed signs of infectious pancreatic necrosis, including mortality (authors' unpublished data).…”
Section: Discussionmentioning
confidence: 99%